2010
DOI: 10.1044/1092-4388(2010/09-0068)
|View full text |Cite
|
Sign up to set email alerts
|

Swallow Characteristics in Patients With Oculopharyngeal Muscular Dystrophy

Abstract: This investigation provides further insight into the swallow function of patients with myopathic disease. Muscle fiber loss leads to weakness, which results in reductions in swallow function and quality of life. Weight and endurance are not greatly altered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 29 publications
2
34
1
6
Order By: Relevance
“…Our participants' tongue strength following oral endotracheal extubation (30.9 ± 14.7 to 36.7 ± 11.4 kPa) was substantially weaker than that reported for patients with Parkinson disease (44.3 ± 3.2 to 55.1 ± 13.8 kPa) [7,14], patients with oral and oropharyngeal cancer following primary radiotherapy with or without chemotherapy (37.1 ± 14.4 to 56.7 ± 9.35 kPa) [8,9], but not patients with oculopharyngeal muscular dystrophy (26.8 ± 7.8 kPa) [10]. Most importantly, tongue weakness for our participants after endotracheal extubation was comparable to the lower end of tongue strength for patients with swallowing difficulty (31.0 ± 15.9 to 48.3 ± 13.8 kPa [11,15], reiterating the need for clinical intervention.…”
Section: Tongue Motor Function Following Prolonged Oral Intubationcontrasting
confidence: 63%
See 1 more Smart Citation
“…Our participants' tongue strength following oral endotracheal extubation (30.9 ± 14.7 to 36.7 ± 11.4 kPa) was substantially weaker than that reported for patients with Parkinson disease (44.3 ± 3.2 to 55.1 ± 13.8 kPa) [7,14], patients with oral and oropharyngeal cancer following primary radiotherapy with or without chemotherapy (37.1 ± 14.4 to 56.7 ± 9.35 kPa) [8,9], but not patients with oculopharyngeal muscular dystrophy (26.8 ± 7.8 kPa) [10]. Most importantly, tongue weakness for our participants after endotracheal extubation was comparable to the lower end of tongue strength for patients with swallowing difficulty (31.0 ± 15.9 to 48.3 ± 13.8 kPa [11,15], reiterating the need for clinical intervention.…”
Section: Tongue Motor Function Following Prolonged Oral Intubationcontrasting
confidence: 63%
“…To avoid response burden, we took the best performance reading out of two trials after one practice trial. Test-retest reliability was 0.76-0.99 [2,[6][7][8][9][10][11].…”
Section: Data Abstractionmentioning
confidence: 99%
“…Etiologic correlates associated with decreased lingual strength include cerebrovascular accident (CVA; Hori, Ono, Iwata, Nokubi, & Kumakura, 2005;Konaka et al, 2010), muscular dystrophy (HamanakaKondoh et al, 2014;Palmer, Neel, Sprouls, & Morrison, 2010), Parkinson's disease (Unemoto, Tsuboi, Kitashima, Furuya, & Kikuta, 2011), and oropharyngeal cancer (Lazarus, 2006;Lazarus et al, 2000). Although individuals in these diagnostic categories are potential candidates for lingual strength training, their outcomes are likely variable given factors related to the underlying nature of their diagnoses (e.g., remitting, progressive) and any concomitant interventions needed for disease treatment (e.g., radiation therapy).…”
Section: Intervention Protocols and Target Populationsmentioning
confidence: 99%
“…Thus, the decrease in tongue pressure observed in some cases of stroke was basically associated with the presence of dysphagia. Several studies in the literature have related the decrease in tongue pressure to the symptom of dysphagia (10,20,21,22,23,24) . The results of this study indicated that tongue pressure in the subjects affected with stroke could trigger dysphagia.…”
Section: Discussionmentioning
confidence: 99%